2019
DOI: 10.25267/commons.2019.v8.i2.02
|View full text |Cite
|
Sign up to set email alerts
|

Concienciar en sostenibilidad tecnológica: experiencias comunicativas y educativas en España para un uso sostenible de las TIC.

Abstract: Information and Communication Technologies are usually presented as neutral in environmental terms, highlighting their benefits in comparison with other energy sources very frequently. However, its material impact increases due to the exponential growth observed both in the populations incorporated to its daily consumption and in the intensity with which they are used. This article departs from this fact aiming to identify and analyze various experiences that, from the fields of Education and Communication, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Perceived obsolescence is an additional phenomenon: certain people consider their devices to be outdated, usually leading them to dispose of them shortly after use [21]. We must add to these factors a reduction in the price of technological products and the effectiveness of extensive marketing and advertising campaigns [19]. This early disposal of digital technology is reflected in an average duration of mobile device usage of approximately two years [22].…”
Section: Technological Progress and Its Counterpart: The Importance Omentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived obsolescence is an additional phenomenon: certain people consider their devices to be outdated, usually leading them to dispose of them shortly after use [21]. We must add to these factors a reduction in the price of technological products and the effectiveness of extensive marketing and advertising campaigns [19]. This early disposal of digital technology is reflected in an average duration of mobile device usage of approximately two years [22].…”
Section: Technological Progress and Its Counterpart: The Importance Omentioning
confidence: 99%
“…These initiatives, all of which focus on the developing sustainability, include scales to assess the contribution of educational digital resources to sustainable behavior [16], proposals to include the SDG in educational curriculums [17], teacher training program designs [12] and methodological strategies such as place-based learning to work on principles of Education for Sustainable Development (ESD) [18]. Research has also addressed other educational levels, as indicated in the Dieste et al [17] study, focusing on the inclusion of the SDGs in the Primary and Secondary Education curriculum or schemes for the reuse of technological devices in educational settings [19]. All these works highlight the multidisciplinary strengths of ESD [18] and the impact of teacher training on the sustainable use of technology by future generations.…”
Section: Introductionmentioning
confidence: 99%
“…Una competencia digital imprescindible para la construcción de una ciudadanía "que conoce y asume sus responsabilidades y participa activamente conforme a ellas, en todas sus dimensiones: política, económica, social, cultural" (Tucho, 2006, p.84). Desde esta posición, el impacto medioambiental de los dispositivos TIC ha de desempeñar un papel primordial en el contexto actual de crisis medioambiental y, por tanto, en toda definición de competencia digital (López, 2014(López, , 2020(López, , 2021García-de-Madariaga et al, 2019).…”
Section: La Competencia Digital Docente Para Un Consumo Sostenible De...unclassified
“…Las discusiones indican que este patrón genera conflicto de intereses porque, tal como hemos discutido en el desarrollo de la perspectiva teórica, la necesidad de salud ecológica es una necesidad básica universal. Esto significa que un consumo orientado a satisfacer el bienestar materialista que perjudica la calidad del aire y del agua, y genera competencia por los recursos naturales, es un consumo que entraña conflicto de intereses tanto para consumidores del "primer mundo" como entre estos y personas que habitan territorios explotados para la extracción de recursos naturales o convertidos en vertederos (Madariaga Miranda et al, 2019). Para el grupo participante en la indagación de la fase conceptual de la IAP, este conflicto se entrelaza con el conflicto entre los objetivos de la industria de obtener beneficios y las necesidades de bienestar integral de personas con poder adquisitivo.…”
Section: Autonomía Interdependienteunclassified